FOOTBALL AS AN OBJECT OF STUDY OF THE SOCIAL SCIENCES (Fiep Bulletin - online, 2015)
The present article analyses the classical problem that the historical studies that attempt to analyze football face. From this reality, a challenge to the new approaches being currently produced is proposed. The methodological option was to present the problem of the way the social/human sciences analyze the mass cultural phenomena. After reviewing the methodological proposal of different authors it was possible to point out to the necessity of seeking methodological elements that make the "irrationality" of this theme to be turned into an object of study, which will certainly point out the necessity of multidisciplinary works.
Keywords: History of football; Sports Sociology; Mass Sports.